9A.01: HYPERURICEMIA IS AN INDEPENDENT DETERMINANT OF ARTERIAL STIFFNESS. (June 2015) - Antza, C.; Papakatsika, S.; Kotronis, G.; Mikoudi, K.; Stabouli, S.; Kotsis, V.
Abstract : Objective: The aim of the study was to identify determinants of arterial stiffness in patients with increased uric acid levels. Design and method: 280 consecutive subjects (51.4% male) aged 52.98 ± 22.9 years were included in the study. Subjects were never treated before for hypertension or uric acid. A physician measured office BP three times in each subject using a mercury sphygmomanometer. All subjects underwent 24h-ABPM on a usual working day. Pulse wave velocity (PWV) was measured after 15 min of rest in the supine position. The subject was not speaking or sleeping in a quiet, semi-darkened, temperature-controlled laboratory. Participants had been advised to refrain from eating, smoking and drinking caffeine beverages and alcohol before measurement. PWV was calculated as the transit time of the arterial pulse along the carotid-femoral distance divided with the distance measured directly. Results: Carotid-femoral PWV was independently associated (ANCOVA analysis) with age (B = 0.13, P < 0.001), 24 h average SBP (B = 0.07, P < 0.05) and uric acid (B = 0.72, P < 0.001), but not with office BP values, e-GFR, lipid levels, gender and BMI. Carotid-femoral PWV was found 8.215 ± 0.41 m/sec (SE) in patients with normal uric acid values and 10.252 ± 0.91 m/sec (SE) in patients with hyperuricemia after adjustment for age, gender, office BP, 24 h SBP, 24 h pulse pressure, e-GFR, fasting serum cholesterol, triglycerides and BMI. The difference in carotid-femoral PWV between normal uric acid subjects and hyperuricemic patients was 2.037 ± 1.008 m/sec (SE). This difference was statistically significant at the 0.05 level after Bonferroni's adjustment for multiple comparisons. Conclusions: Arterial stiffness was found increased in patients with hyperuricemia suggesting a role for increased uric acid in the pathophysiology of large arteries arteriosclerosis independent of age, gender, obesity, blood pressure levels and kidney function.